X-Men. The last stand [videorecording (DVD)] - Ratner, Brett; Jackman, Hugh; Berry, Halle; McKellen, Ian (20th Century Fox Home Entertainment, 2006)
With the help of their new recruits, The Beast and Angel, the X-Men must face evolution itself in the form of their former teammate, Jean Grey. Possessed with the cosmic power of the Dark Phoenix, the resurrected Jean Grey has become a danger to herself, her mutant comrades, and the entire planet. A potential cure is discovered and processed to treat and ultimately eliminate the genetic mutations, once and for all. As the battle lines are drawn, the X-Men must contend with both Jean Grey's world-consuming powers, as well as the malevolent Brotherhood.